Titanium aluminum lithium phosphate, method for preparing the same, and use thereof
Patent Information
- Application Number
- CN202511072766.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-07-31
AI Technical Summary
[0004]鉴于背景技术中存在的技术问题,本申请提供了一种磷酸钛铝锂及其制备方法与应用,旨在解决现有磷酸钛铝锂的制备工艺难以实现高结晶度的纳米级材料的技术问题
[0021]第二方面,本申请实施例提供了一种磷酸钛铝锂,由第一方面所述的磷酸钛铝锂的制备方法制得,所述磷酸钛铝锂的离子电导率≥6.00×10-4S/cm。
Smart Images

Figure CN120964752B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid-state battery technology, specifically to a lithium titanium aluminum phosphate, its preparation method, and its application. Background Technology
[0002] With the rapid development of the new energy vehicle industry, solid-state batteries are an important development direction for power batteries due to their high energy density, excellent safety, and long cycle life. However, solid-state batteries still face many challenges, such as the ionic conductivity of solid electrolytes, the stability of the electrode / electrolyte interface, and high cost. Lithium titanium aluminum phosphate has significant application value in the field of solid-state batteries due to its good ionic conductivity and chemical stability.
[0003] Currently, the main preparation processes for lithium titanium aluminum phosphate include solid-state sintering and sol-gel methods. These methods generally have some limitations, typically requiring sintering at temperatures above 700℃ to obtain lithium titanium aluminum phosphate materials with good crystallinity. However, high-temperature sintering easily leads to particle growth, making it difficult to prepare nanoscale lithium titanium aluminum phosphate particles. If the sintering temperature is too low, although particle growth can be suppressed, the crystallinity of lithium titanium aluminum phosphate will be affected, thus impacting its ionic conductivity and chemical stability. Summary of the Invention
[0004] In view of the technical problems existing in the background art, this application provides a lithium titanium aluminum phosphate, its preparation method and application, aiming to solve the technical problem that the existing preparation process of lithium titanium aluminum phosphate is difficult to achieve highly crystalline nanoscale materials.
[0005] In a first aspect, embodiments of this application provide a method for preparing lithium titanium aluminum phosphate, comprising the following steps: Titanium source, lithium source, aluminum source and phosphorus source are added to solvent to obtain a mixed solution; The mixture is heated to a first preset temperature, an oxidant is added, and then the temperature is raised to a second preset temperature to obtain the initial product through reaction. The primary product is sequentially filtered, washed, and dried to obtain the intermediate product. The intermediate product was mixed with an additive and then calcined to obtain lithium titanium aluminum phosphate.
[0006] In the technical solution of this application embodiment, lithium titanium aluminum phosphate is prepared by mixing titanium, lithium, aluminum, and phosphorus sources, heating, oxidation, filtration, washing, drying, and calcination. The operation process is relatively simple and easy to industrialize and scale up. By controlling the first and second preset temperatures, the reaction can be carried out under relatively mild conditions, avoiding harsh conditions such as high temperature and high pressure, which is beneficial for equipment selection and maintenance. Simultaneously, the filtration, washing, and drying steps effectively remove impurities generated during the reaction, ensuring that the final lithium titanium aluminum phosphate has high purity and meets the requirements of subsequent applications. Furthermore, by adding additives and performing calcination, the crystal structure and performance of lithium titanium aluminum phosphate can be optimized.
[0007] In some embodiments, the molar ratio of the titanium source, the lithium source, the aluminum source, and the phosphorus source is 1.7:(1.35~1.5):(0.3~0.5):(3.1~3.5).
[0008] In this embodiment, by precisely controlling the molar ratio of the four elements—titanium, lithium, aluminum, and phosphorus—a specific molar ratio helps reduce the occurrence of side reactions, thereby improving the purity of the target product, lithium titanium aluminum phosphate. This results in a lithium titanium aluminum phosphate material with a more uniform composition and a more stable structure, which is beneficial for improving its physical and chemical properties and thus for its use in the field of solid-state batteries. At the same time, a reasonable molar ratio makes the crystal structure of the prepared lithium titanium aluminum phosphate more stable, which is conducive to its long-term stable operation under high temperature, high pressure, or strong electrolyte environments.
[0009] In some embodiments, the titanium source is one or more of tetrabutyl titanate, isopropyl titanate, and tetraethyl titanate; and / or, the lithium source is one or more of lithium acetate, lithium nitrate, and lithium acetate; and / or, the aluminum source is one or more of aluminum acetate and aluminum nitrate; and / or, the phosphorus source is phosphorous acid; and / or, the solvent is one or more of anhydrous ethanol, isopropanol, and ethylene glycol.
[0010] In this embodiment, organotitanium compounds such as tetrabutyl titanate, isopropyl titanate, and tetraethyl titanate exhibit high reactivity, promoting the reaction and increasing the reaction rate and yield. Lithium salts such as lithium acetate, lithium nitrate, and lithium acetate have good solubility in the selected solvents, facilitating the formation of a homogeneous mixed solution, thereby improving the homogeneity and purity of the final product. Aluminum sources such as aluminum acetate and aluminum nitrate are readily soluble and react in the selected solvents, helping to control reaction conditions, avoid side reactions, and improve the selectivity of the target product. Phosphorous acid, as a phosphorus source, can provide the required phosphorus element, and its specific chemical properties help optimize the structure and performance of the product, enhancing its performance in specific applications. Solvents such as anhydrous ethanol, isopropanol, and ethylene glycol have low toxicity and volatility, minimizing the impact on the environment and operators, and conforming to the principles of green chemistry. In this application, by selecting appropriate raw materials and solvents, the generation of by-products can be reduced, the purity of the target product lithium aluminum titanium phosphate can be improved, and application requirements can be met.
[0011] In some embodiments, the first preset temperature is 70~90℃; and / or, the second preset temperature is 180~250℃; and / or, the reaction pressure is 2~5MPa, and the reaction time is 15~30h.
[0012] In this embodiment, preheating of the mixture at the first preset temperature facilitates the complete dissolution of the raw materials and the initiation of the reaction; at the second preset temperature, the reaction rate accelerates, which is beneficial for the formation of the target product. A higher second preset temperature helps promote the complete reaction and reduces the presence of unreacted raw materials. Simultaneously, within the aforementioned pressure range, the activity of the reactants and the reaction rate can be increased, side reactions can be suppressed, and product purity can be improved. Therefore, in this application, under suitable temperature and pressure, the reaction time can be shortened to 15-30 hours, improving production efficiency and reducing production costs.
[0013] In some embodiments, the oxidant is hydrogen peroxide; and / or, the concentration of the oxidant is 10~30wt%; and / or, the molar ratio of the oxidant to the phosphorus source is (1.2~1.5):1.
[0014] In this embodiment, hydrogen peroxide, acting as an oxidant, effectively oxidizes the reactants and promotes the formation of the target product. Furthermore, by controlling the concentration of hydrogen peroxide, the intensity of the oxidation reaction can be precisely controlled, avoiding over-oxidation or under-oxidation. The molar ratio of the oxidant to the phosphorus source helps ensure sufficient reaction of the phosphorus source, improving product purity.
[0015] In some embodiments, the auxiliary agent is one or more of ammonium carbonate, ammonium acetate, and oxalic acid.
[0016] In this embodiment, the additive decomposes at high temperature, which can hinder particle growth and fusion, optimize crystal structure and morphology, and improve the electrochemical performance of lithium titanium aluminum phosphate.
[0017] In some embodiments, the mass ratio of the adjuvant to the intermediate product is (0.1~0.15):1.
[0018] In this embodiment, an appropriate amount of additive can effectively promote crystal growth and structural optimization. Excessive additive may lead to the generation of too much gas during calcination, resulting in a loose material structure and affecting its mechanical strength and electrochemical performance. Too little additive may not be able to fully exert its function.
[0019] In some embodiments, the calcination treatment temperature is 400~600℃, the heating rate is 100~200℃ / h, and the holding time is 4~10h; and / or, the calcination atmosphere is air or oxygen.
[0020] In this embodiment, a suitable calcination temperature facilitates the full reaction of the components in the intermediate product and the growth of crystals, forming a well-crystallized lithium titanium aluminum phosphate material; an appropriate heating rate can avoid temperature gradient stress caused by excessively rapid heating, prevent material cracking, and ensure the uniformity of the calcination process; a holding time of 4 to 10 hours is sufficient to allow the reaction to proceed fully and the crystal structure to stabilize, thereby improving the electrochemical performance of the material; calcination in an air or oxygen atmosphere can further oxidize and remove residual organic matter and impurities, improving the purity of the final product.
[0021] Secondly, embodiments of this application provide a lithium titanium aluminum phosphate, prepared by the method for preparing lithium titanium aluminum phosphate described in the first aspect, wherein the lithium titanium aluminum phosphate has an ionic conductivity ≥ 6.00 × 10⁻⁶. -4 S / cm.
[0022] In the technical solution of this application embodiment, by optimizing the preparation method, the obtained lithium titanium aluminum phosphate material has high ionic conductivity, which can significantly improve the rate performance and cycle stability of lithium-ion batteries and extend the battery's service life.
[0023] Thirdly, embodiments of this application provide a battery including a positive electrode, a negative electrode, and an electrolyte, wherein the electrolyte includes lithium aluminum titanium phosphate as described in the second aspect.
[0024] In this embodiment, the battery contains the aforementioned lithium titanium aluminum phosphate material, thus possessing advantages such as high power density, long cycle life, high energy efficiency, and excellent rate performance.
[0025] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0026] To more clearly illustrate the technical solutions of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.
[0027] Figure 1 A flowchart illustrating the preparation method of lithium titanium aluminum phosphate provided in this application embodiment; Figure 2 This is a SEM image of lithium titanium aluminum phosphate provided in Example 1 of this application; Figure 3 SEM image of lithium aluminum titanium phosphate provided in Comparative Example 1 of this application; Figure 4 The images show the XRD patterns of lithium titanium aluminum phosphate provided in Example 1 and Comparative Example 1 of this application. Detailed Implementation
[0028] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0030] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0031] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0032] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0033] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).
[0034] Currently, the main preparation processes for lithium titanium aluminum phosphate include solid-state sintering and sol-gel methods. These methods generally have some limitations, typically requiring sintering at temperatures above 700℃ to obtain lithium titanium aluminum phosphate materials with good crystallinity. However, high-temperature sintering easily leads to particle growth, making it difficult to prepare nanoscale lithium titanium aluminum phosphate particles. If the sintering temperature is too low, although particle growth can be suppressed, the crystallinity of lithium titanium aluminum phosphate will be affected, thus impacting its ionic conductivity and chemical stability.
[0035] To address the technical challenge of achieving highly crystalline nanoscale materials using existing lithium titanium aluminum phosphate preparation processes, this application provides a lithium titanium aluminum phosphate, its preparation method, and its application. By optimizing the raw material ratio and processing technology, the technical effects of improving product crystallinity, reducing particle size, and enhancing ionic conductivity can be achieved, thereby improving the cycle stability and rate performance of the battery.
[0036] Please refer to Figure 1 In a first aspect, embodiments of this application provide a method for preparing lithium titanium aluminum phosphate, comprising the following steps: S1. Add titanium source, lithium source, aluminum source and phosphorus source to solvent to obtain a mixed solution; S2. Heat the mixture to a first preset temperature, add an oxidant, and then heat it to a second preset temperature to obtain the initial product through reaction; S3. The initial product is sequentially filtered, washed and dried to obtain the intermediate product; S4. The intermediate product is mixed with the additives and then calcined to obtain lithium titanium aluminum phosphate.
[0037] In this application, the raw materials are fully dissolved and mixed to form a homogeneous mixture. The mixture is then heated to a first preset temperature to activate the reactants and bring them to a reactive state. Subsequently, an oxidant is added, and the temperature is raised to a second preset temperature to allow the reactants to react fully. The oxidant provides oxygen atoms to participate in the oxidation reaction, promoting the formation of primary products from titanium, lithium, aluminum, and phosphorus. The solid primary product is separated from the liquid by filtration to remove unreacted raw materials and byproducts. The surface-adhered impurities and solvents are further removed by washing and drying to obtain an intermediate product. Finally, the intermediate product is mixed with an additive and calcined at a high temperature. The additive decomposes at high temperature, hindering particle growth and fusion, to obtain highly crystalline nano-sized titanium aluminum lithium phosphate. The first and second preset temperatures are both less than 250°C. Preferably, the first preset temperature is less than 100°C and the second preset temperature is less than 250°C.
[0038] Furthermore, in some embodiments, the molar ratio of titanium source, lithium source, aluminum source and phosphorus source is 1.7:(1.35~1.5):(0.3~0.5):(3.1~3.5).
[0039] In this application, a suitable molar ratio ensures the accuracy of the chemical composition, avoids the formation of other byproducts, and optimizes the purity and performance of the target product. Specifically, the molar ratio of the titanium source, lithium source, aluminum source, and phosphorus source can be any value within the range of 1.7:1.35:0.3:3.1, 1.7:1.45:0.4:3.25, 1.7:1.5:0.5:3.5, or 1.7:(1.35~1.5):(0.3~0.5):(3.1~3.5).
[0040] Furthermore, in some embodiments, the titanium source is one or more of tetrabutyl titanate, isopropyl titanate, and tetraethyl titanate; and / or, the lithium source is one or more of lithium acetate, lithium nitrate, and lithium acetate; and / or, the aluminum source is one or more of aluminum acetate and aluminum nitrate; and / or, the phosphorus source is phosphorous acid; and / or, the solvent is one or more of anhydrous ethanol, isopropanol, and ethylene glycol.
[0041] In this application, the titanium source is an organic titanate ester, which has high purity, reducing the possibility of introducing impurity phases. The lithium and aluminum sources have good solubility, ensuring the uniform distribution of lithium and aluminum elements in the solution. The preferred lithium and aluminum sources are lithium acetate and aluminum acetate. During the reaction, the anion is acetate ion, and the weak acid produced is acetic acid, which has little impact on the final synthesis of lithium titanium aluminum phosphate. The phosphorus source is phosphorous acid, which is soluble in alcohol solvents and exists in a solid state, facilitating transportation and storage. After forming a solution, it achieves ionic-level mixing of lithium, phosphorus, titanium, and aluminum, significantly enhancing the mixing scale compared to physical mixing and other mixing methods. Alcohol solvents can achieve higher dispersion and higher pressure, making it easier to promote the hydrothermal synthesis of lithium titanium aluminum phosphate. Specifically, the amount of solvent added is 3 to 5 times the total mass of the titanium, lithium, aluminum, and phosphorus sources.
[0042] Furthermore, in some embodiments, the first preset temperature is 70~90℃; and / or, the second preset temperature is 180~250℃; and / or, the reaction pressure is 2~5MPa, and the reaction time is 15~30h.
[0043] In this application, the first preset temperature helps the titanium, lithium, aluminum, and phosphorus sources to dissolve or disperse more fully, forming a uniform mixture; the second preset temperature promotes more thorough hydrolysis and condensation reactions of titanium and aluminum alkoxides, forming a more stable and complex oxide or hydroxide network structure; high pressure conditions help maintain the liquid phase reaction, accelerate the reaction process, and promote the formation of more uniform and crystallized primary products; the reaction time ensures that the precursor reaction is sufficient and uniform; through the synergistic effect of process parameters, it helps to control the rate, extent, and pathway of the chemical reaction, providing high-quality intermediate products for subsequent calcination steps.
[0044] Specifically, the first preset temperature can be 70℃, 80℃, 90℃, or any value within the range of 70~90℃; the second preset temperature can be 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, or any value within the range of 180~250℃; the reaction pressure can be 2MPa, 3MPa, 4MPa, 5MPa, or any value within the range of 2~5MPa; and the reaction time can be 15h, 18h, 20h, 22h, 25h, 28h, 30h, or any value within the range of 15~30h.
[0045] Furthermore, in some embodiments, the oxidant is hydrogen peroxide; and / or, the concentration of the oxidant is 10~30wt%; and / or, the molar ratio of the oxidant to the phosphorus source is (1.2~1.5):1.
[0046] In this application, adding hydrogen peroxide at a certain temperature oxidizes phosphoric acid to phosphoric acid. Simultaneously, the water in the hydrogen peroxide hydrolyzes the titanium source into highly reactive titanium hydroxide, better promoting the phase transformation of lithium titanium aluminum phosphate and forming crystal nuclei for precipitation transformation. This helps to better control the primary particle size and morphology of lithium titanium aluminum phosphate, making it easier to obtain lithium titanium aluminum phosphate with a primary particle size in the nanometer range and a concentrated particle size distribution. A suitable hydrogen peroxide concentration ensures sufficient reactivity to complete its function. If the hydrogen peroxide concentration is too low, the oxidation capacity will be insufficient, failing to effectively complete the required oxidation steps or resulting in a slow reaction rate. Conversely, if the hydrogen peroxide concentration is too high, the reaction will be too vigorous and difficult to control, increasing the risk of side reactions. Furthermore, by controlling the molar ratio of the oxidant to the phosphorus source, it can be ensured that the phosphorus source can be fully oxidized, promoting the formation of the lithium titanium aluminum phosphate precursor. Specifically, the molar ratio of the oxidant to the phosphorus source can be any value within the range of 1.2:1, 1.35:1, 1.5:1, or (1.2~1.5):1.
[0047] Furthermore, in some embodiments, the additive is one or more of ammonium carbonate, ammonium acetate, and oxalic acid.
[0048] In the technical solution of this application embodiment, the additive decomposes at high temperature, hindering the growth and fusion of particles, which helps to reduce the final grain size of lithium titanium aluminum phosphate.
[0049] Furthermore, in some embodiments, the mass ratio of the adjuvant to the intermediate product is (0.1~0.15):1.
[0050] In this application, a suitable mass ratio helps the additives to completely decompose and volatilize during the subsequent sintering process without introducing significant impurities. Simultaneously, the decomposition process promotes the formation and crystallization of the lithium aluminum titanium phosphate phase, resulting in a dense and uniform final product. Specifically, the mass ratio of the additive to the intermediate product can be any value within the range of 0.1:1, 0.12:1, 0.15:1, or (0.1~0.15):1.
[0051] Furthermore, in some embodiments, the calcination temperature is 400~600℃, the heating rate is 100~200℃ / h, and the holding time is 4~10h; and / or, the calcination atmosphere is air or oxygen.
[0052] In this application, calcination treatment can improve the crystallinity of the material. At the same time, compared with the conventional sintering temperature, the sintering temperature of this application is significantly reduced, and the sintering time is also significantly shortened. This can reduce the final grain size of lithium titanium aluminum phosphate and obtain nanoscale lithium titanium aluminum phosphate. Furthermore, because this application is sintered at a low temperature, it is easier to break down, avoiding the difficulty in breaking down caused by high-temperature sintering and the need for equipment such as ball mills. This application can achieve control of ultra-fine particle size through airflow pulverization.
[0053] Secondly, embodiments of this application provide a lithium titanium aluminum phosphate, prepared by the method for preparing lithium titanium aluminum phosphate described in the first aspect, wherein the lithium titanium aluminum phosphate has an ionic conductivity ≥ 6.00 × 10⁻⁶. -4 S / cm.
[0054] In the technical solution of this application embodiment, the obtained lithium titanium aluminum phosphate has higher ionic conductivity, smaller and more concentrated primary particle size, and moderate BET, making it suitable as a solid electrolyte.
[0055] Secondly, embodiments of this application provide a battery including a positive electrode, a negative electrode, and an electrolyte, wherein the electrolyte includes lithium aluminum titanium phosphate as described in the third aspect.
[0056] In the technical solution of this application embodiment, the battery contains the above-mentioned lithium titanium aluminum phosphate material, and therefore has the advantages of high power density, long cycle life, high energy efficiency and excellent rate performance.
[0057] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0058] I. Preparation Method Example 1 This embodiment provides a method for preparing lithium titanium aluminum phosphate, including the following steps: S1. Dry lithium acetate, aluminum acetate, and phosphorous acid in a vacuum drying oven until the moisture content is less than 0.1%. Add tetrabutyl titanate, lithium acetate, aluminum acetate, and phosphorous acid to anhydrous ethanol in a molar ratio of 1.7:1.45:0.4:3.25. The mass of anhydrous ethanol is 4 times the total mass of tetrabutyl titanate, lithium acetate, aluminum acetate, and phosphorous acid. Stir well to obtain a mixture. S2. Pour the mixture into a high-pressure reactor, heat to 80°C, and introduce hydrogen peroxide with a concentration of 20 wt% while stirring at a speed of 200 r / min for 90 min. The amount of hydrogen peroxide added is 1.35 times the molar amount of phosphorous acid. After adding the hydrogen peroxide, heat to 210°C and continue stirring and reacting at a pressure of 3.2 MPa for 20 h. Then, cool down and release the pressure to obtain the initial product. S3. Filter and wash the primary product, and dry the filter residue to obtain the intermediate product; S4. Mix the intermediate product with ammonium carbonate, the mass of which is 0.12 times the mass of the intermediate product. Then, pulverize the mixture to a particle size of 2.1 μm. Calcinate the mixture with air, maintaining the ammonia content in the furnace below 5 ppm during the calcination process. The heating rate during calcination is 150℃ / h. After holding at 500℃ for 7 hours, cool to room temperature and pulverize using an air jet mill at a pulverizing pressure of 0.4 MPa and a classifying wheel frequency of 25 Hz. The resulting product has a particle size of 0.35 μm. Vacuum package the product to obtain lithium titanium aluminum phosphate.
[0059] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 1. Detection results of lithium titanium aluminum phosphate obtained in Example 1 Example 2 This embodiment provides a method for preparing lithium titanium aluminum phosphate. The only difference from Example 1 is that the molar ratio of tetrabutyl titanate, lithium acetate, aluminum acetate and phosphorous acid is 1.7:1.35:0.3:3.1.
[0060] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 2. Detection results of lithium titanium aluminum phosphate obtained in Example 2 Example 3 This embodiment provides a method for preparing lithium titanium aluminum phosphate. The only difference from Example 1 is that the molar ratio of tetrabutyl titanate, lithium acetate, aluminum acetate and phosphorous acid is 1.7:1.5:0.5:3.5.
[0061] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 3. Detection results of lithium titanium aluminum phosphate obtained in Example 3 Example 4 This embodiment provides a method for preparing lithium titanium aluminum phosphate. Compared with Example 1, the only difference is that the mass of ammonium carbonate is 0.1 times the mass of the intermediate product.
[0062] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 4. Detection results of lithium titanium aluminum phosphate obtained in Example 4 Example 5 This embodiment provides a method for preparing lithium titanium aluminum phosphate. Compared with Example 1, the only difference is that the mass of ammonium carbonate is 0.15 times the mass of the intermediate product.
[0063] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 5. Detection results of lithium titanium aluminum phosphate obtained in Example 5 Example 6 This embodiment provides a method for preparing lithium titanium aluminum phosphate. Compared with Example 1, the only difference is that the calcination temperature is 400℃ and the holding time is 4h.
[0064] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 6. Detection results of lithium titanium aluminum phosphate obtained in Example 6 Example 7 This embodiment provides a method for preparing lithium titanium aluminum phosphate. The only difference from Example 1 is that the calcination temperature is 600℃ and the holding time is 10h.
[0065] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 7. Detection results of lithium titanium aluminum phosphate obtained in Example 7 Example 8 This embodiment provides a method for preparing lithium titanium aluminum phosphate. Compared with Example 1, the only difference is that the amount of hydrogen peroxide added is 1.2 times the molar amount of phosphorous acid.
[0066] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 8. Detection results of lithium titanium aluminum phosphate obtained in Example 8 Example 9 This embodiment provides a method for preparing lithium titanium aluminum phosphate. The only difference from Example 1 is that the amount of hydrogen peroxide added is 1.5 times the molar amount of phosphorous acid.
[0067] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 9. Detection results of lithium titanium aluminum phosphate obtained in Example 9 Comparative Example 1 Comparative Example 1 provides a method for preparing lithium titanium aluminum phosphate, comprising the following steps: S1. Nano-titanium dioxide, nano-alumina, ammonium dihydrogen phosphate, and battery-grade lithium carbonate are mixed in the molar ratio of titanium source, lithium source, aluminum source, and phosphorus source as in Example 1, which is 1.7:1.45:0.4:3.25. After slurrying with water, the mixture is ground to a particle size of 200 nm, spray-dried, calcined at 900 °C for 12 h, and then pulverized by air jet milling to a particle size of 2.7 μm. The mixture is then added to a sand mill for sand milling to obtain lithium titanium aluminum phosphate.
[0068] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 10 Detection results of lithium titanium aluminum phosphate obtained in Comparative Example 1 Comparative Example 2 Comparative Example 2 provides a method for preparing lithium titanium aluminum phosphate, which differs from Example 1 only in that ammonium carbonate is not added.
[0069] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 11 Detection results of lithium titanium aluminum phosphate obtained in Comparative Example 2 Comparative Example 3 Comparative Example 2 provides a method for preparing lithium titanium aluminum phosphate. The only difference from Example 1 is that the mass of ammonium carbonate is 0.2 times the mass of the intermediate product.
[0070] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 12 Detection results of lithium titanium aluminum phosphate obtained in Comparative Example 3 Comparative Example 4 Comparative Example 4 provides a method for preparing lithium titanium aluminum phosphate. The only difference from Example 1 is that the calcination temperature is 350°C and the holding time is 7 hours.
[0071] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 13 shows the detection results of lithium aluminum titanium phosphate obtained in Comparative Example 4. Comparative Example 5 Comparative Example 5 provides a method for preparing lithium titanium aluminum phosphate. The only difference from Example 1 is that the calcination temperature is 650°C and the holding time is 7 hours.
[0072] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 14 Detection results of lithium aluminum titanium phosphate obtained in Comparative Example 5 Comparative Example 6 Comparative Example 6 provides a method for preparing lithium titanium aluminum phosphate. The only difference from Example 1 is that the amount of hydrogen peroxide added is 1.1 times the molar amount of phosphorous acid.
[0073] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 15 Detection results of lithium aluminum titanium phosphate obtained in Comparative Example 6 Comparative Example 7 Comparative Example 7 provides a method for preparing lithium titanium aluminum phosphate, which differs from Example 1 only in that the amount of hydrogen peroxide added is 1.6 times the molar amount of phosphorous acid.
[0074] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 16 Detection results of lithium aluminum titanium phosphate obtained in Comparative Example 7 Comparative Example 8 Comparative Example 8 provides a method for preparing lithium titanium aluminum phosphate. Compared with Example 1, the only difference is that in step S2, the heating is not carried out in stages, but hydrogen peroxide is directly added and the temperature is raised to 210°C.
[0075] Specifically, the test results for lithium titanium aluminum phosphate are as follows: Table 17 Detection results of lithium aluminum titanium phosphate obtained in Comparative Example 8 II. Testing Methods 1. SEM testing The lithium titanium aluminum phosphate prepared in Example 1 and Comparative Example 1 were analyzed by SEM using a MERLIN Compact field emission scanning electron microscope (model: Quanta200FEG) manufactured by Zeiss.
[0076] 2. XRD test The lithium titanium aluminum phosphate prepared in Examples 1 and Comparative Example 1 was detected using X-ray diffraction.
[0077] 3. Particle size test The particle size of lithium titanium aluminum phosphate prepared in the examples and comparative examples was tested using a laser particle size analyzer.
[0078] 4. BET Test The specific surface area of lithium titanium aluminum phosphate prepared in the examples and comparative examples was tested using the nitrogen adsorption BET test method.
[0079] 5. Elemental Analysis The metal element content in lithium titanium aluminum phosphate prepared in the examples and comparative examples was determined by inductively coupled plasma atomic emission spectrometry.
[0080] 6. Ionic conductivity The ionic conductivity of lithium titanium aluminum phosphate prepared in the examples and comparative examples was tested by AC impedance spectroscopy.
[0081] 7. Mechanical performance testing The mechanical properties of the diaphragm were tested using a universal testing machine.
[0082] III. Analysis of Test Results for Each Embodiment and Comparative Example Figures 2 to 3 The images show SEM images of lithium titanium aluminum phosphate obtained in Example 1 and Comparative Example 1, respectively. It can be seen that the lithium titanium aluminum phosphate particles obtained in Example 1 are more concentrated and have a spherical shape. Figure 4 The XRD patterns of lithium titanium aluminum phosphate provided in Example 1 and Comparative Example 1 of this application show that Comparative Example 1 has a certain impurity phase, which is lithium titanium phosphate enriched from titanium.
[0083] As can be seen from Tables 1 to 17, the lithium titanium aluminum phosphate obtained in the embodiments of this application has higher ionic conductivity, smaller and more concentrated primary particle size, and moderate BET. Comparative Example 1, using a conventional preparation method, has lithium titanium aluminum phosphate with lower BET specific surface area and ionic conductivity, and uneven particle distribution. Comparative Example 2 did not add ammonium carbonate, resulting in excessively large grain size. Comparative Example 3, with excessive ammonium carbonate, generated too much gas during calcination, resulting in a loose material structure and low bulk density. Comparative Example 4, with its lower calcination temperature, can reduce the grain size of lithium titanium aluminum phosphate, but the crystal structure is unstable, leading to a decrease in electrochemical performance. Comparative Example 5, with its excessively high calcination temperature... The increased firing temperature led to an increase in grain size; in Comparative Example 6, insufficient hydrogen peroxide resulted in incomplete oxidation of some reactants, leading to an incomplete crystal structure of lithium titanium aluminum phosphate and a decrease in ionic conductivity; in Comparative Example 7, excessive hydrogen peroxide caused over-oxidation of the target product, damaging the crystal structure and surface properties, and reducing the specific surface area of lithium titanium aluminum phosphate due to over-oxidation, affecting its electrochemical performance; in Comparative Example 8, hydrogen peroxide was added directly without staged heating, resulting in uneven dispersion of raw materials and rapid heating leading to local overheating or uncontrolled reaction, causing unreacted or partially reacted components in the initial product, resulting in insufficient crystallinity and uneven particle distribution in the final product, and a decrease in ionic conductivity.
[0084] The lithium aluminum titanium phosphate obtained in the examples and comparative examples was compressed into tablets at a pressure of 3T for 1 minute in a tablet press. After being removed, the tablets were calcined at 1000℃ for 3 hours. Samples of the resulting films were taken, and the thickness of each film was 10 mm. The impedance, maximum force, tensile strength, and elongation at maximum force were measured. The results are as follows: Table 18 Detection results of lithium aluminum titanium phosphate membranes The data above shows that the lithium titanium aluminum phosphate provided in this application has low impedance, high tensile strength, and strong toughness, indicating better conductivity and excellent mechanical strength, making it suitable as a high-performance solid-state electrolyte. This application achieves a comprehensive improvement in material performance through optimized process parameters, providing reliable technical support for applications such as solid-state batteries.
[0085] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A method for preparing lithium titanium aluminum phosphate, characterized in that, Includes the following steps: Titanium source, lithium source, aluminum source and phosphorus source are added to solvent to obtain a mixed solution; The mixture is heated to a first preset temperature, an oxidant is added, and then the temperature is raised to a second preset temperature to obtain the initial product through reaction. The primary product is sequentially filtered, washed, and dried to obtain the intermediate product. The intermediate product was mixed with an additive and then calcined to obtain lithium titanium aluminum phosphate. The second preset temperature is higher than the first preset temperature; The oxidant is hydrogen peroxide, the concentration of the oxidant is 10~30wt%, and the molar ratio of the oxidant to the phosphorus source is (1.2~1.5):1; The auxiliary agent is one or more selected from ammonium carbonate, ammonium acetate, and oxalic acid; the mass ratio of the auxiliary agent to the intermediate product is (0.1~0.15):1; The calcination temperature is 400~600℃.
2. The method for preparing lithium titanium aluminum phosphate according to claim 1, characterized in that, The molar ratio of the titanium source, the lithium source, the aluminum source, and the phosphorus source is 1.7:(1.35~1.5):(0.3~0.5):(3.1~3.5).
3. The method for preparing lithium titanium aluminum phosphate according to claim 2, characterized in that, The titanium source is one or more of tetrabutyl titanate, isopropyl titanate, and tetraethyl titanate; and / or The lithium source is one or more of lithium acetate, lithium nitrate, and lithium acetate; and / or The aluminum source is one or more of aluminum acetate and aluminum nitrate; and / or The phosphorus source is phosphorous acid; and / or The solvent is one or more of anhydrous ethanol, isopropanol, and ethylene glycol.
4. The method for preparing lithium titanium aluminum phosphate according to claim 1, characterized in that, The first preset temperature is 70~90℃; and / or The second preset temperature is 180~250℃; and / or The reaction is carried out at a pressure of 2-5 MPa for 15-30 hours.
5. The method for preparing lithium titanium aluminum phosphate according to claim 1, characterized in that, The calcination treatment involves a heating rate of 100~200℃ / h and a holding time of 4~10h; and / or The calcination atmosphere is air or oxygen.
6. A lithium titanium aluminum phosphate, characterized in that, The lithium titanium aluminum phosphate is prepared by the method according to any one of claims 1-5, wherein the lithium titanium aluminum phosphate has an ionic conductivity ≥ 6.00 × 10⁻⁶. -4 S / cm.
7. A battery comprising a positive electrode, a negative electrode, and an electrolyte, characterized in that, The electrolyte includes lithium titanium aluminum phosphate as described in claim 6.
Citation Information
Patent Citations
Titanium aluminum phosphate, preparation method thereof and lithium titanium aluminum phosphate electrolyte material
CN118458723A
KR20250007158A